باعتماد المدرج التكراري RGB تحسين الصور الملونة نوع - رنا زهير جرجيس (PROSPECTIVE RESEARCHES, 2023)
Many researches have depended on histogram in improving the gray pictures and showed good results in this field. Since there are many color patterns of colored pictures, its depending on histogram on the purpose of improvement is different. In this study, a (RGB) colored picture was decomposed into the main colors (Red, Green and Blue), then it was independently improved in that it was of gray gradient in order to be recomposed after that. Then, the resulting colorful image was compared with original image depending on the improvement observed on the colors of image via calculating the Euclidian dimension for both pictures. The pictures produced from the adopted algorithm showed significant results in order to study the data which are available inside those pictures, which leads to reveal the information hidden in the origin image, This may encourage using such algorithm with other patterns of colors (HSL, SMYK..etc).